TRANSFORMATION OF STUDENTS' UNDERSTANDING OF LINEAR MOTION SUB-MATERIALS THROUGH ASSEMBLR EDU LEARNING MEDIA AT THE JUNIOR HIGH SCHOOL LEVEL/MTS STUDENTS - Lailita Nur Azizah; Andi Suhardi (Science Education, Institut Agama Islam Negeri Ponorogo, 2026)
Science instruction on the topic of linear motion often leads to misconceptions because the concepts of position, velocity, and acceleration are abstract and dynamically interrelated. The prevalence of formula-based instruction causes students to tend to understand concepts procedurally without being able to relate them to physical phenomena. The use of Augmented Reality (AR)-based media, such as Assemblr Edu, has the potential to help visualize concepts in a more concrete and interactive way. This study aims to describe the transformation of students’ conceptual understanding of the linear motion subtopic through the use of AR media. Unlike previous studies that mainly focus on learning outcomes, this study specifically examines the process of conceptual transformation based on the framework of Conceptual Change Theory. The research focuses on: (1) students’ initial understanding, (2) the process of understanding transformation during learning, and (3) students’ final understanding. This study employs a descriptive qualitative approach with subjects comprising a science teacher and six eighth-grade students in Class VIII C at MTsN 1 Lumajang. Data were collected through observation, interviews, and documentation, and analysed using thematic coding based on stages of conceptual change, with validity ensured through source and technique triangulation. The findings indicate that students’ initial understanding is dominated by procedural patterns and conceptual misconceptions. During instruction, AR visualization triggered cognitive conflict that encouraged conceptual restructuring through visual exploration, social interaction, and teacher facilitation. Students’ final understanding developed into a more conceptual and applied form, as evidenced by their ability to explain relationships between variables and apply them in real-life contexts. These findings suggest that the integration of AR with appropriate pedagogical support facilitates meaningful and relatively stable conceptual change. This study implies that AR-based learning should be designed not only as a visualization tool, but as a structured pedagogical strategy to support students’ conceptual development.